EFEKTIFITAS MODEL PROJECT BASED LEARNING (PJBL) BERBASIS STEAM UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA SD - Wulantri Handayani; Bambang Subali; Nuni Widiarti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
For scientific students, It is believed that the Project Based Learning (PjBL) paradigm is suitable. This method introduces STEM concepts to kids in an effort to strengthen their critical thinking skills. In today's globalized society, critical thinking abilities are crucial for kids to thrive. This study aims to assess how successfully STEM-based Project Based Learning (PjBL) models support students' critical thinking development at the primary school level. For the inquiry, a one-group pretest-posttest quasi-experimental approach was chosen. The study involved Grade VI students from the Gajah Mada cluster in the Pangkah subdistrict. Purposeful sampling was used to choose 23 students from SD Negeri Depok 02 for the experimental group and 33 students from SD Negeri Depok 01 for the control group.The tools used in the study were the critical thinking and student response questionnaires. Ten multiple-choice questions with explanations made up the critical thinking exam. There were fifteen items on the questionnaire, as well. A STEM project centred on series and parallel electrical circuits was being worked on by the kids. Responses from the students suggested that STEM-based PjBL learning was well-received. The experimental class's N-Gain test result was 0.60, which puts it in the medium category; the control class's result was 0.40, which is likewise in the medium range. The completion rate for while the control class only reached 87.50%, the experimental class achieved 95.83%. The findings of this study show that the STEAM-based Project Based Learning (PjBL) method greatly enhances the critical thinking skills of elementary school children.